1976
DOI: 10.1111/j.1365-2044.1976.tb11738.x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular changes during laparoscopy

Abstract: There have been several reports of cardiac output measurements during laparoscopy for gynaecological purposes, using dye dilution techniques. Techniques for measuring cardiac output which involve arterial and central venous cannulation did not seem appropriate to us in healthy patients undergoing a relatively minor surgical procedure. It was therefore decided to measure cardiac output during laparoscopy using a Minnesota Impedance C a r d i~g r a p h .~-~ This is a non-invasive technique which enables repeated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
1

Year Published

1992
1992
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(24 citation statements)
references
References 7 publications
0
23
0
1
Order By: Relevance
“…Fortunately, despite rather signi®cant hemodynamic depression associated with laparoscopy, clinical complications related to these eects are rare [3,6,17]. Several authors have reported consistent decreases in CI related to pneumoperitoneum [2,3,7,9,12]. Many of these have been as great as 30%.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Fortunately, despite rather signi®cant hemodynamic depression associated with laparoscopy, clinical complications related to these eects are rare [3,6,17]. Several authors have reported consistent decreases in CI related to pneumoperitoneum [2,3,7,9,12]. Many of these have been as great as 30%.…”
Section: Discussionmentioning
confidence: 97%
“…The adverse hemodynamic eects of the pneumoperitoneum during laparoscopic cholecystectomy (LC) have been well documented [2,4,9,11]. Initial studies of pneumoperitoneum were carried out in young women undergoing brief gynecologic procedures and hemodynamic eects were modest [2,8].…”
Section: Abstract: Laparoscopic Cholecystectomy ð Hemodynamics ð Pnementioning
confidence: 99%
“…Pneumoperitoneum has consistently been shown to increase mean arterial pressure, heart rate, and central venous pressure [3,4]. Decreases in cardiac output as great as 30% have been reported as well; however, most of these studies were conducted in young healthy women undergoing brief gynecologic procedures [2,7,11,12].…”
mentioning
confidence: 97%
“…Lenz et al [9] established a correlation between cardiac depression and the amount of abdominal carbon dioxide used. It was also stated that the 15 mm Hg abdominal carbon dioxide pressure results in elevated MAP, SVR and reduced stroke volume [9]. Stroke volume reduction is the result of a combination of a depressant effect of carbon dioxide on myocardial contractility and the rise in afterload.…”
Section: Discussionmentioning
confidence: 99%